2013
DOI: 10.5539/jmr.v5n4p26
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Layered Suspension Blood Flow Through a Composite Stenosis

Abstract: Blood flow in the presence of a composite stenosis is investigated by examining the effects that red cell concentration, stenosis height and a peripheral layer have on blood flow characteristics. A two-layered model with a particle-fluid suspension in the core region and a peripheral plasma layer without any particles is used to represent blood. Expressions for three flow characteristics (impedance, wall shear stress and shear stress at the stenosis throat) are derived. Flow impedance increases with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Simpson's rule was used on the integrals which needed to be evaluated numerically. Plots for these solutions were provided using [8,13,18,19,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpson's rule was used on the integrals which needed to be evaluated numerically. Plots for these solutions were provided using [8,13,18,19,21].…”
Section: Resultsmentioning
confidence: 99%
“…Tripathi and Kumar Sharma [17] explored MHD flow of blood through an inclined porous artery with heat transfer using a Newtonian fluid model. However due to the nature of blood, a two-layered model is suitable for examining flow in microcirculation [18,19]. The effect of heat transfer on two-layered blood flow through a composite stenosis in the presence of a magnetic field has been researched by Sankar, Rao Gunakala and Comissiong [20] but the permeability of the vessel wall was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…[7] discussed that if a low WSS area is less than 0.5Pa then the risk of intimal thickening for an artery will be very high. [8] investigated that instead of using a time-dependent electromagnetic field, in most clinical devices static magnetic field formed by an everlasting magnet to treat vascular infections. [9] examined the progression of blood impacted by an outside magnetic field with diminishing the seeping during surgeries; drop the recuperating of fractures and effectiveness for the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Shukla et al [6]1980 Singh , Joshi & Joshi, 2014 [8] and Joshi & Gadkari [1] taken stenosis shaped as cosine, trapezium and triangular respectively and investigated plasma layer viscosity effect on flow characteristics. Sankar & Gunakala [4] have studied the fluid flow through small composite constricted vessels using a twolayered model applying uniform transverse external magnetic field and found that flux of blood and velocity both reduced with increasing of intensity of applied magnetic field . Recently Neeraja et al…”
Section: Introductionmentioning
confidence: 99%